Management of patients with rheumatoid arthritis in real clinical practice: Switching from interleukin 6 receptor inhibitors to interleukin 6 inhibitor (olokizumab) - A. A. Baranov; I. B. Vinogradova; O. N. Anoshenkova; O. V. Antipova; E. A. Bogdanova; Y. Y. Grabovetskaya; E. P. Ilivanova; A. N. Kalyagin; I. N. Kushnir; N. A. Lapkina; M. V. Mokrousova; O. B. Nesmeyanova; et al. (Научно-практическая ревматология, 2023)
Aim. Switching to another biologic with the same mode of action provides greater opportunity for long-term management of patients with rheumatoid arthritis (RA). In clinical practice, especially in the context of the COVID-19 pandemic, such switching occurred for non-medical reasons as well. However, there is no information about switching from interleukin 6 (IL-6) receptor (R) inhibitor to direct IL-6 inhibitor. Objective – to assess the efficacy and safety of therapy in RA patients, after switching from IL-6R inhibitors (tocilizumab (TOC), sarilumab (SAR)) to olokizumab (OKZ) for reasons not related to the loss of their efficacy or adverse events. Material and methods. In this retrospective cohort study efficacy parameters and routine biochemical data were analyzed using descriptive statistics – mean values with standard deviation for continuous parameters and absolute and relative frequency for binary variables. Adverse events (AE) were reported according to patient’s files. The statistical significance and changes of the analyzed variables by visits were determined using paired t-test. Fisher’s exact test or chi-square test was used to compare the proportion of patients with improvement/no change and of patients with worsening. All tests were 2-sided, and p<0.050 was considered statistically significant. As this was an observational study, the statistical criteria have not been pre-specified. Results. We analyzed results obtained during 5 visits (2 visits before switching, switching visit and 2 visits after switching) in 110 RA patients who switched to OKZ 64 mg every 4 weeks subcutaneously (SC). Most patients (79.1%) were women, and 70% of patients were both positive by rheumatoid factor and antibodies to cyclic citrullinated peptide. Mean RA duration was 11 [6; 16] years, previous treatment duration was 44 [27; 62] months and mean interval before switching to OKZ was 35 [31; 68] days. This relatively long interval led to an increase in DAS28-ESR (Disease Activity Score 28 with determination of erythrocyte sedimentation rate) from 2.4 [1.9; 3.0] to 2.6 [2.1; 3.5] and DAS28-CRP (DAS28 with determination of C-reactive protein level) from 2.8 [2.0; 3.3] to 2.9 [2.2; 4.0] (the trends were similar in patients who received combined therapy and monotherapy). After switching, all of RA symptoms and indexes have been improved compared with the switching visit (some of them were significantly better even compared with stable therapy period e. g. DAS28-CRP was 2.4 [2.0; 3.1] in the overall group and 2.4 [2.1; 2.7] in the monotherapy group). AEs were registered in only 7 (6.4%) patients, of which 1 (0.9%) case (an exacerbation of herpes infection) was considered as serious. The most frequent AEs were arthralgia and mild transient leukopenia (2 patients each). There were no deaths. Conclusion. OKZ effectively maintained remission/low activity of RA after switching in both regimens: as add-on to disease modifying anti-rheumatic drugs and as monotherapy, and did not cause any additional safety concerns. The optimal results were reported when intervals before switching to OKZ were closer to those indicated in the instructions for IL-6R inhibitors.